Comportamiento germinativo y potencial forrajero de Setaria magna (Poaceae). - Marinoni, Lorena del Rosario (2013)
Germinative behavior and forage potential of Setaria magna (Poaceae). Setaria magna Griseb. is an American species that grows well in damp, swampy environments either in fresh or salt water. It is an annual, grass with vigorous plants in their natural habitat. In this study the germinative behavior as well as the forage potential of this species were evaluated. Caryopses viability and their germination ability at different temperature regimes were analyzed, by means of different scarification treatments and temperatures from diverse environments and harvest times. Morphological and productive traits in genotypes of a population in vegetative and reproductive states were evaluated in field. Results showed that caryopses viability remained the same during the first year after harvest and then decreased. Covered caryopses did not germinate at any of the temperatures tested, which suggests dormancy, whereas in naked caryopses alternating temperature allowed a greater percentage and velocity of germination. Some morphological traits differed significantly among genotypes on the vegetative state, while no differences were found regarding reproductive state. Biomass quality varied between genotypes and states and proved to be similar to that cited for other widely cultivated species of the same cycle. The results obtained suggest the possibility of domestication of this species.